G-CSF plus azacitidine versus azacitidine alone for patients with high-risk myelodysplastic syndrome: academic, open label, randomized trial - Stopka, Tomáš; Minařík, Lubomír; Dusilková, Nina; Pešta, Michal; Kulvait, Vojtěch; Špaček, Martin; Zemanová, Zuzana; Kalousová, Marta; Jonášová, Anna (Blood cancer journal, 2022)
GA trial is registered under EudraCT#: 2013-001639-38.
Keywords: faktor stimulující kolonie granulocytů; Myelodysplastic Syndromes; Antimetabolites, Antineoplastic; lidé; Granulocyte Colony-Stimulating Factor; myelodysplastické syndromy; azacytidin; Azacitidine; protinádorové antimetabolity; Humans